2015
DOI: 10.1038/cgt.2015.38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upregulation of Id3 in human lung adenocarcinoma cells on proliferation, apoptosis, mobility and tumorigenicity

Abstract: The inhibitor of DNA-binding/differentiation 3 (Id3) protein is a helix-loop-helix transcription factor and may have an important role in cell proliferation and differentiation. This study was to evaluate the effects of upregulation of Id3 in human lung adenocarcinoma cells on proliferation, apoptosis, mobility and tumorigenicity. Short interference RNA suppression of Id3 (miRId3) in A549 cells was used to investigate the functional role(s) of Id3. Next, we used in vitro wound-healing assay and trans-well assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…A549 human lung adenocarcinoma epithelial cells and that ectopic overexpression of Id3 in A549 cells inhibited their proliferation and induced apoptosis in vitro, as well as reducing tumor growth in vivo (13,14). These results suggested that Id3, as an upstream gene of the apoptotic signaling cascade, can induce cell apoptosis.…”
Section: Upregulation Of Id3 Inhibits Cell Proliferation and Induces mentioning
confidence: 83%
See 1 more Smart Citation
“…A549 human lung adenocarcinoma epithelial cells and that ectopic overexpression of Id3 in A549 cells inhibited their proliferation and induced apoptosis in vitro, as well as reducing tumor growth in vivo (13,14). These results suggested that Id3, as an upstream gene of the apoptotic signaling cascade, can induce cell apoptosis.…”
Section: Upregulation Of Id3 Inhibits Cell Proliferation and Induces mentioning
confidence: 83%
“…Numerous studies have assessed the role of Id3 in various cancer types (25,26). Previous studies by our group have shown that upregulation of Id3 inhibited the proliferation and induced apoptosis in A549 cells in vitro and in vivo (13,14), while further study is required to determine the underlying mechanisms. Therefore, ectopic expression of Id3 may represent a novel strategy for treating NSCLC.…”
Section: Discussionmentioning
confidence: 96%
“…It is reported that overexpressed Id3 inhibited cell proliferation and induced apoptosis and may be a potential target for tumor suppression [52]. Here, downregulated Id3 may activate cell proliferation, such as T cell, macrophages and may be a potential drug for immunodeficiency therapy.…”
Section: Effects Of Fenps On the Expression Of Id Genesmentioning
confidence: 99%
“…The EA.hy926 cells were cultivated in DMEM supplemented with 10% FBS and 1% penicillin/streptomycin, and incubated at 37°C in a 5% CO 2 -humidified atmosphere. 19,20 The B16 cells were cultured under the same conditions, in RPMI 1640 medium. Cells were subcultured at ~80% confluence.…”
mentioning
confidence: 99%
“…Finally, affinity kinetic data between CS-ES2-AF and ES2-AF to CD44 were tested by a single-loop experiment according to the wizard program in the operating system, and the affinity of the two drugs for CD44 was compared. 19,[32][33][34] Bioimaging of FITc-labeled cs-es2-aF conjugate…”
mentioning
confidence: 99%